2018
DOI: 10.1093/pcp/pcy014
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Glutamine Synthetase Isozymes Play Redundant Roles in Ammonium Assimilation Under Low-Ammonium Conditions in Roots of Arabidopsis thaliana

Abstract: Ammonium is a major nitrogen source for plants; it is assimilated into glutamine via a reaction catalyzed by glutamine synthetase (GLN). Arabidopsis expresses four cytosolic GLN genes, GLN1; 1, GLN1; 2, GLN1; 3 and GLN1; 4, in roots. However, the function and organization of these GLN1 isozymes in ammonium assimilation in roots remain unclear. In this study, we aimed to characterize the four GLN1 isozymes. The levels of growth of the wild type and gln1 single and multiple knockout lines were compared in a hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…The reason why the total GS activity was unchanged in the shoots of the gln1;2 mutants under low-nitrate while the GS1 protein content showed a decrease can be explained by the fact that GLN1;2 has low affinity for ammonium ( Ishiyama et al , 2004 ). Nevertheless, the lower GS1 activity in roots under both low- and high-nitrate conditions could explain the smaller rosette size observed in the triple-mutant, ( Konishi et al , 2017 , 2018 ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The reason why the total GS activity was unchanged in the shoots of the gln1;2 mutants under low-nitrate while the GS1 protein content showed a decrease can be explained by the fact that GLN1;2 has low affinity for ammonium ( Ishiyama et al , 2004 ). Nevertheless, the lower GS1 activity in roots under both low- and high-nitrate conditions could explain the smaller rosette size observed in the triple-mutant, ( Konishi et al , 2017 , 2018 ).…”
Section: Resultsmentioning
confidence: 94%
“… Guan et al (2015) showed that seed production and germination were impaired in the gln1;2 single and the gln1;2 - gln1;1 double knock-out mutants. As a result of grafting experiments, Guan and Schjoerring (2016) proposed that the prominent role of GLN1;2 was in the shoot; however, in their studies, Konishi et al (2017 , 2018 ) showed that both GLN1;2 and GLN1;3 are essential for ammonium assimilation in the roots.…”
Section: Introductionmentioning
confidence: 99%
“…Barley mutants lacking GS2 were unable to grow under normal atmospheric conditions as they were not able to re-assimilate photorespiratory ammonium and accumulated relatively high levels of ammonium in the leaves (Blackwell et al, 1987;Wallsgrove et al, 1987). GS1 plays a role in primary NH 4 + assimilation in the roots (Funayama et al, 2017;Guan et al, 2016;Konishi et al, 2018) and is, in addition, involved in the assimilation and recycling of NH 4 + released from protein degradation during senescence (Avila-Ospina et al, 2014;Bernard and Habash, 2009;Krapp, 2015). Individual GS1 isoforms may exert different functions reflecting their kinetic properties and expression patterns.…”
Section: Introductionmentioning
confidence: 99%
“…However, the overexpression of nitrite reductase (NiR) and nitrate reductase (NR) in tobacco and Arabidopsis decreases nitrate levels in plant tissues but fail to improve the biomass or grain yield [ 12 , 20 ]. The ectopic expression of cytoplasmic glutamine synthetase1 (GS1) [ 21 ] and glutamine synthetase 2 (GS2) [ 22 , 23 ] have some positive effects on plant biomass and grain yield. Studies suggest that targeted manipulation of one gene or just one component of the N signaling pathway may not be enough to significantly improve overall NUE because it is a quantitative trait controlled by many genes and interacting regulatory pathways that are linked with the actual NUE of a crop plant [ 24 ].…”
Section: Introductionmentioning
confidence: 99%